2020
DOI: 10.22226/2410-3535-2020-3-351-360
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of metal-graphene composites by molecular dynamics: a review

Abstract: Fabrication of the new composite materials with improved mechanical characteristics is of high interest nowadays. Simulation methods can considerably improve understanding of the interaction between the graphene and metal phase, even in the atomistic level. In the present work, the simulation of graphene-metal composites by molecular dynamics is reviewed. Both experiments and simulation results have shown that the metal matrix can be reinforced with graphene flakes, and the overall mechanical properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…Most of the previous studies on metal/graphene composites were aimed to understand the technological issues, such as fabrication of the composites or improving adhesion between graphene and metal. [15,[23][24][25][26] However, the study of the effect of morphology of the structure and the mechanical properties of metal/graphene composites are also of high importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies on metal/graphene composites were aimed to understand the technological issues, such as fabrication of the composites or improving adhesion between graphene and metal. [15,[23][24][25][26] However, the study of the effect of morphology of the structure and the mechanical properties of metal/graphene composites are also of high importance.…”
Section: Introductionmentioning
confidence: 99%
“…This method was previously used for studying of crumpling of graphene nanoribbons, [27] CG, [5][6][7]28] polycrystalline CG, [29] metal-graphene composites. [23,30,31] In this work, several graphene/metal nanocomposites are designed and investigated after high-temperature deformation treatment. The initial size of Ni nanoparticle, the effect of DOI: 10.1002/pssr.202100429…”
Section: Introductionmentioning
confidence: 99%
“…The initial structure is compressed at 1000 K to obtain graphene–nickel composite material (c, c’). Composite can be fabricated under hydrostatic compression at high temperatures [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, the other approach to obtain the Ni-graphene composite was applied: introducing metal nanoparticles to the crumpled graphene matrix. In [ 41 , 42 , 43 , 44 ] it was shown that such composites can be obtained through compression combined with high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, theoretical scientific research based on molecular dynamics (MD) simulation is widely used. The simulation allows us to analyze at the atomic level the dislocations evolution at the Cu/graphene interface [ 24 , 44 ], to estimate the tensile capacity of carbon nanotube/Al composites [ 45 ], to study the effect of aluminum orientation on the strengthening mechanisms of graphene/Al composites [ 46 ], and to predict the existence of metal/graphene composites based on crumpled graphene [ 39 , 47 ] and much more. Using MD simulation, it was also found that the addition of carbon materials (such as graphene or carbon nanotubes) to a metal matrix leads to its strengthening [ 26 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%